2003
DOI: 10.1161/01.cir.0000047060.60595.cc
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Reduces the Ability of Clopidogrel to Inhibit Platelet Aggregation

Abstract: Background-We observed that the prodrug clopidogrel was less effective in inhibiting platelet aggregation with coadministration of atorvastatin during point-of-care platelet function testing. Because atorvastatin is metabolized by cytochrome P450 (CYP) 3A4, we hypothesized that clopidogrel might be activated by CYP3A4. Methods and Results-Platelet aggregation was measured in 44 patients undergoing coronary artery stent implantation treated with clopidogrel or clopidogrel plus pravastatin or atorvastatin, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
435
14
17

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(481 citation statements)
references
References 38 publications
15
435
14
17
Order By: Relevance
“…26,27 Lau and colleagues sought to determine whether variations in CYP3A4 activity contribute to clopidogrel variability in platelet inhibition by measuring platelet aggregation in 32 patients undergoing PCI with stenting and 35 healthy volunteers. 28 According to the degree of ADPinduced platelet aggregation, 22% and 16% were classified as clopidogrel nonresponders, 32% and 12% as low responders, and 47% and 72% as responders among patients and healthy volunteers, respectively; an inverse correlation was found between platelet activation and CYP3A4 activity (p = 0.003).…”
Section: Clopidogrelmentioning
confidence: 99%
“…26,27 Lau and colleagues sought to determine whether variations in CYP3A4 activity contribute to clopidogrel variability in platelet inhibition by measuring platelet aggregation in 32 patients undergoing PCI with stenting and 35 healthy volunteers. 28 According to the degree of ADPinduced platelet aggregation, 22% and 16% were classified as clopidogrel nonresponders, 32% and 12% as low responders, and 47% and 72% as responders among patients and healthy volunteers, respectively; an inverse correlation was found between platelet activation and CYP3A4 activity (p = 0.003).…”
Section: Clopidogrelmentioning
confidence: 99%
“…In subgroup analysis of patients using atorvastatin, which is lipophilic and is reportedly competes with clopidogrel for the cytochrome P450 system, 19,20 groups B and C showed superior P2Y 12 inhibition to group A. The difference in P2Y 12 inhibition between groups B and C did not exceed the predetermined limit of noninferiority ( Figure 6).…”
Section: Adverse Eventmentioning
confidence: 97%
“…Some investigators have reported that differences in lipophilicity of statins may influence the antiplatelet action of clopidogrel. 19,20 We therefore decided to control the statin used to avoid potential controversy in interpretation of data.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Agents that inhibit the CYP3A4 and CYP2C19 enzyme systems can counter the action of clopidogrel by preventing its conversion to active metabolites from a pro-drug state. Atorvastatin has been demonstrated to attenuate the antiplatelet activity of clopidogrel in a dose-dependent manner [44]. However, this has not been shown to affect clinical events in the post hoc analysis of the Clopidogrel for the Reduction of Events During Observation (CREDO) trial [45].…”
Section: Antiplatelet Resistancementioning
confidence: 99%